Implementasi Kebijakan Sekolah Ramah Anak Dalam Mewujudkan Kota Layak Anak di Kota Depok - Safitri Ridwan Rangkuti; Irfan Ridwan Maksum (Publik : (Jurnal Ilmu Administrasi), 2019)
Child-friendly and child-based schools are an effort to fulfill children's rights and provide quality education for children. This study aims to explain the implementation of Child Friendly School Policies established by the Ministry of Female Empowerment and Child Protection and to analyze the supporting and inhibiting factors for the implementation of Child Friendly School Policies in SMP Negeri 6 Depok. This study used a qualitative method that shows the implementation of the Child Friendly School Policy in SMPN 6 Depok been going well, assessed in the context of the process, results (output), impact (outcomes) and causality (causal connection).The factors that support the implementation of the Child Friendly School Policy at SMP Negeri 6 Depok are good and smooth communication, attitudes and commitment of all school people, coordination between the Depok Government and the School and the positive support of all school members, parents, surrounding communities. However, there are still obstacles, namely the limited school budget and the number of teachers, and the density of teacher activities that have caused the implementation of policies to be not optimal. For facilitating the implementation of child-friendly school policies, collaboration between central government and local government, schools and communities is needed. Sekolah yang ramah anak dan berbasis hak anak merupakan upaya memenuhi hak-hak anak dan memberi pendidikan yang berkualitas bagi anak. Penelitian ini bertujuan untuk menjelaskan implementasi Kebijakan Sekolah Ramah Anak yang ditetapkan oleh Kementerian Pemberdayaan Perempuan dan Perlindungan Anak dan menganalisis faktor pendukung dan penghambat implementasi Kebijakan Sekolah Ramah Anak di Kota Depok. Penelitian ini menggunakan metode kualitatif yang menunjukan implementasi Kebijakan Sekolah Ramah Anak di SMP Negeri 6 Depok sudah berjalan baik, dinilai dalam konteks proses, hasil (output), dampak (outcome) dan hubungan sebab akibat (causal connection). Faktor-faktor yang mendukung implementasi Kebijakan Sekolah Ramah Anak di Kota Depok adalah komunikasi yang baik dan lancar, sikap dan komitmen seluruh warga sekolah, koordinasi antar Pemda Depok dengan Sekolah serta adanya dukungan positif seluruh warga sekolah, orang tua, masyarakat sekitar. Namun masih terdapat faktor penghambat yaitu terbatasnya anggaran sekolah dan jumlah guru serta padatnya aktivitas guru menyebabkan pelaksanaan kebijakan belum optimal. Untuk memperlancar implementasi kebijakan sekolah ramah anak dibutuhkan kerjasama antara seluruh pihak baik pemerintah pusat dan daerah, sekolah dan masyarakat